Characterization and topical delivery of phenylethyl resorcinol - Zhang, Yanling; Sil dos Santos, Bruno; Kung, Chin-Ping; Hadgraft, Jonathan; Heinrich, Michael; Sinko, Balint; Lane, Majella E. (Wiley, 2019)
Objective: Phenylethyl resorcinol (PR) has been used widely in the personal care industry as a novel skin lightening ingredient. Surprisingly, there is only limited information describing the physicochemical properties of this active. Therefore, the primary objective of this study was to perform a comprehensive characterization of PR. A secondary objective was to investigate the delivery of this molecule to mammalian skin.